UAV Based Data Gathering in Wireless Sensor Networks - Ali, Zain Anwar; Masroor, Suhaib; Aamir, Muhammad (Wireless personal communications, 2019)
Recently, Wireless sensor networks (WSNs) have turned out to be a dominant subject of research due to its application areas. Moreover, with the integration of Unmanned Aerial Vehicle (UAV) in the loop, WSN becomes more valuable and interested topic among research community. With the addition of UAV in WSN, life span of WSN is increased and communication between WSN and Network Control Centre becomes more efficient. UAVs not only increased the life of the network, but also reduce the data processing and memory related issues in the network. In this paper, we address the problem of data gathering from a WSN with altitude controlled UAV. Simulation results verify the effectiveness of our proposed method.